A companion to Plautus - Franko, George Fredric; Dutsch, Dorota (Blackwell companions to the ancient world., 2020)
"This reference resource will offer a comprehensive survey of the plays of Rome's most popular dramatist. The surviving scripts of Titus Maccius Plautus (along with those of his successor Terence) provide the primary source of the Western Comic theatrical tradition for the Middle Ages, Renaissance, modern era, and today's newer media of movies and television sitcoms. The Companion will explore the distinctive features of Plautus' dramaturgy, how those features relate to their Roman environment, and how they have inspired subsequent dramatists"--